1995
DOI: 10.1172/jci118276
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cultured vascular endothelial cells by antiphospholipid antibodies.

Abstract: Circulating antiphospholipid antibodies (aPL) are associated with a syndrome of thrombosis, recurrent fetal loss, and thrombocytopenia. We have demonstrated the activation of cultured human umbilical vein endothelial cells (HUVEC) by IgG from patients with anticardiolipin antibodies (aCL).Incubation of HUVEC for 4 h with purified IgG (100 jig/ ml) from patients with high-titer aCL induced a 2*3-fold increase in monocyte adhesion over that seen in HUVEC incubated with IgG's from normal subjects. The effect of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
255
0
9

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(278 citation statements)
references
References 27 publications
12
255
0
9
Order By: Relevance
“…Several studies have demonstrated that aPL activate ECs in vitro, suggesting a mechanism by which these antibodies exert procoagulant properties (15,49,50). Utilizing a mouse model, our group has previously demonstrated that aPL antibodies increase leukocyte adhesion to ECs of cremasteric muscle postcapillary venules, suggesting that these antibodies induce activation of ECs in vivo and that these effects correlate with enhanced thrombus formation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that aPL activate ECs in vitro, suggesting a mechanism by which these antibodies exert procoagulant properties (15,49,50). Utilizing a mouse model, our group has previously demonstrated that aPL antibodies increase leukocyte adhesion to ECs of cremasteric muscle postcapillary venules, suggesting that these antibodies induce activation of ECs in vivo and that these effects correlate with enhanced thrombus formation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Some aPL bind to endothelial cells, suggesting that aPL may interact with endothelial cells and thus promote thrombosis (68,69). APTs can bind to immobilized PS in the presence of calcium and prothrombin (28,29), and a LAC IgG preparation can enhance the binding of prothrombin to endothelial cells and increase thrombin generation on these cells (45), suggesting that APT may concentrate prothrombin on cell surface phospholipids and thus lead to a hypercoagulable state.…”
Section: Pathogenic Role Of Aptsmentioning
confidence: 99%
“…The nature of the cell surface "receptor" for P,GPI is not known. Antibody binding to &GPI on the endothelial cell surface induced the expression of the adhesion molecules E-selectin, vascular cell adhesion molecule-1, and intercellular adhesion molecule-1 (44,89), and enhanced monocyte adhesion to cultured endothelial cells (89).…”
Section: Mechanisms Of Thrombosismentioning
confidence: 99%